Risk assessment in the international food safety policy arena: Can the multilateral institutions encourage unbiased outcomes? - Lee Ann Jackson; Marion Jansen (World Trade Organization (WTO), 2009)
In this paper we provide a description of how food safety related scientific evidence is generated and how it is used in the context of risk assessment for international standard-setting at CODEX and in WTO trade disputes. In particular, we discuss the processes leading to policy conclusions on the basis of scientific evidence, with a focus on the interactions involved between private and public sector actors and those between "scientific experts" and others. We identify weaknesses in the current institutional set-up and provide suggestions on how to improve the interaction between different players at the national and international level so as to strengthen the existing system and increase its cost efficiency.
Keywords: F13; Q16; Q18; 330; Food safety standards; risk assessment; policy capture; Codex Alimentarius Commission; WTO; Nahrungsmittelbelastung; Nahrungsmittelbelastung; Welt